Religious Tolerance and Peace Building in Nigeria: Implications for Community and Socio-Economic Development - Olawale James Gbadeyan (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2023)
This study evaluates how religious tolerance and peace building can impact community and socio-economic development in Nigeria. The paper went historical in tracing the consequences of religious intolerance in Nigeria as well as extract relevant information for the purposes of peace building and harmonious co-existence between Muslims and Christians. The specific objectives shall be to identify the visible causes of religious conflict between Christians and Muslims in Nigeria, evaluate the extent to which religious tolerance will enhance community and socio-economic development, and also to estimate the cost implication of peace building for socio-economic development. The study being a descriptive study engages secondary data, and as well makes recommendation that economic and societal wellbeing can only be achieved in an environment where multi-culturality and multi-religiosity are guaranteed.